Bacteremia with Aerococcus sanguinicola: Case Series with Characterization of Virulence Properties. (23rd May 2014) - Senneby, Erik; Eriksson, Birger; Fagerholm, Erik; Rasmussen, Magnus
Abstract : We describe the clinical presentation of eleven cases with Aerococcus sanguinicola bacteremia. All patients were elderly men and a majority of them had urinary tract abnormalities. All isolates formed biofilm and a majority induced platelet aggregation – two potential virulence mechanisms. Abstract: Background.  Since Aerococcus sanguinicola was designated as a species in 2001, only a few cases of bacteremia have been reported. The aim with this study was to describe the clinical presentation of A sanguinicola bacteremia and to determine the antibiotic susceptibility and the capacity of the bacteria to form biofilm and to induce platelet aggregation. Methods.  Isolates of A sanguinicola from blood cultures were retrospectively identified from 2 clinical microbiology laboratories for 2006 to 2012. Species identity was confirmed through sequencing of the 16S rRNA gene. The medical charts of patients were reviewed. The minimum inhibitory concentration (MIC) for relevant antibiotics was determined. Biofilm formation was measured as the amount of crystal violet absorbed. Platelet aggregation was determined by aggregometry. Results.  Eleven cases of A sanguinicola bacteremia were identified. All patients were male and the median age was 82 years (range 67–93). Nine patients fulfilled criteria for severe sepsis, and 2 patients died at hospital. Two patients were diagnosed with infective endocarditis. Most patients had underlying urinary tract diseases or an indwelling urinary tract catheter. Five patients suffered from dementia. None of the patients was treated with immunosuppressive medications. The MIC values of the isolates were in line with previous reports, with low MICs for penicillin, cefotaxime, and vancomycin. All 11 isolates produced biofilms but not all could induce platelet aggregation. Conclusions.   A sanguinicola can cause severe infections in elderly men with urinary tract abnormalities and the bacteria possess potential virulence mechanisms.